Media Google Classroom dalam Pembelajaran Membaca Memahami Bahasa Jerman - Mardiana Mardiana; Laelah Azizah; Mantasiah R (Phonologie : Journal of Language and Literature, 2021)
Abstract. The purpose of this study is to obtain data and information about the effectiveness of Google Classroom as a learning medium in reading learning to understand German language for students of class XI MIA MAN 1 Makassar. This research is a quasi-experimental research with the form of Nonequivalent Control Group Design. The research population was students of class XI MIA MAN 1 Makassar, the samples in the study were selected randomly (random sampling), which students of class XI MIA 4 as the experimental class and students of class XI MIA 3 as the control class. Data were analyzed using t-test analysis which showed the value of t count = 4.347 ≥ t table = 2.03, with a significance level of 0.05. The results of this study indicate that the Google Classroom learning media is effective in reading learning to understand German language of students in Class XI MAN 1 Makassar.